Odpowiedź :
Szczegółowe wyjaśnienie:
[tex]1)\\2x+5=14,8+(x-3)\\\\2x+5=14,8+x-3\\\\2x+5=11,8+x\qquad|-5-x\\\\\huge\boxed{x=6,8}[/tex]
[tex]2)\\2(3-x)-4(x-5)=2x+2\\\\6-2x-4x+20=2x+2\\\\26-6x=2x+2\qquad|-26-2x\\\\-8x=-24\qquad|:(-8)\\\\\huge\boxed{x=3}[/tex]
[tex]3)\\0,2(10-5x)=3+2(x-1)\\\\2-x=3+2x-2\\\\2-x=1+2x\qquad|-2-2x\\\\-3x=-1\qquad|:(-3)\\\\\huge\boxed{x=\dfrac{1}{3}}[/tex]
[tex]4)\\\dfrac{1}{3}(9-6x)-4=-5(x+1)\\\\3-2x-4=-5x-5\\\\-2x-1=-5x-5\qquad|+1+5x\\\\3x=-4\qquad|:3\\\\\huge\boxed{x=-\dfrac{4}{3}}[/tex]
Odpowiedź:
1) 2x+5= 14,8 + (x-3)
2x +5= 14,8 +x- 3
2x-x= 14,8 -3 -5
x= 6,8
2) 2 ( 3-x) -4 (x-5) = 2x +2
6 -2x-4x + 20= 2x+2
-2x -4x -2x= 2 -6-20
-8x= -16 /:8
x=2
3) 0,2 ( 10-5x)= 3+2 ( x-1)
2- 1x= 3+2x -2
-x-2x= 3-2 -2
-3x= -1 /:3
x=1/3
4) 1/3 (9-6x)-4= -5 (x+1)
3-- 2x -4 = -5x -5
-2x +5x= -5 -3 +4
3x= -4 /:3
x= -4/3= - 1 i 1/3
Szczegółowe wyjaśnienie: